The image of and the interest in the accounting profession: an empirical study in three social groups - Vicente, C.; Laureano, R. M. S.; Machado, M. J. C. V. (International Journal of Business Excellence, 2017)
This study has the following goals: to analyse the image of and the interest in the accounting profession; to identify any possible differences in perception among the respondent groups; to identify the individual characteristics influencing the perception; to propose an explanatory model of the interest in the profession. The respondents were the members of three social groups composing the profession’s value chain: 105 financial officers of the biggest 500 Portuguese companies; 412 chartered accountants; 235 students majoring in Accounting. The data collected show that there are not any significant differences in perception regarding the image of and the interest in the accounting profession. Regarding the influence of the individual characteristics, the results obtained lead to the following conclusion: the third-year students with a higher average perceive a higher level of interest in the profession; the professionals with a higher academic degree and college graduated perceive a lower level of interest in the profession.